Epidemiological aspects, diagnosis, treatment and prevention of ketosis in dairy cows: Review - Delamura, Bruno (Pubvet, 2020)
The transition period in dairy cows has undoubted importance in determining the production cycle, since the period when the animals are susceptible to a wide variety of diseases. Among such diseases, denote a ketosis, a metabolic disease that accommodates high-producing dairy cows and results from an imbalance between the amount of dangerous chemicals during the production cycle and the chemical amounts present in the diet, resulting in the mobilization of corporate reserves for maintenance and milk production, exceeding or limiting hepatic metabolism and resulting in the accumulation of ketone bodies in the body. The diagnosis provides a means of measuring non-esterified fat (AGNES) without blood, milk or urine from affected animals. Solutions based on glucose or its precursors, such as propylene glycol and glucocorticoid therapy, can be used to treat the disease. The nutritional manual for dairy cows during the transition period and the dry period is of fundamental importance to prevent the occurrence of diseases in the milk banks. This review seeks to analyze the respect of the clinical and epidemiological aspects of the disease, as well as its diagnosis, treatment and prevention, in view of the importance of the disease in dairy cattle.
Keywords: dairy cattle; bovine ketosis; transition period